Photovoice's Effect on Students' English Writing Ability - Siregar, Elitaria Bestri Agustina; Widiawati, Yogi; Setiati, Anik Tjandra (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research is based on observations of students in the Industrial Instrumentation and Control study program at Politeknik Negeri Jakarta who show a lack of writing skills, indicating the need for an efficient, useful, and tried method to help them improve their writing talents. Therefore, the purpose of this study is to assess how well the photovoice method improves students' writing skills. This research is a qualitative examination. In accordance with the standard experimental design method of research, the subjects are split into two groups: the experimental group and the control group. The results of the research showed that both the control and experimental classes had a rise in writing skill scores.  According to the statistics, the experimental group that got photovoice saw greater increases in competence than the control group. It is undeniable that applying the photovoice method improves students' writing skills.